2001
DOI: 10.1046/j.1440-169x.2001.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure and developmental expression of Bufo arenarum cellular nucleic acid‐binding protein: Changes in subcellular localization during early embryogenesis

Abstract: A Bufo arenarum cellular nucleic acid-binding protein (bCNBP) full-length cDNA was cloned. bCNBP is a 19.4 kDa protein containing seven CCHC zinc finger motifs, an RGG box and a Ser-rich region. Amino acid comparisons showed high values of homology in vertebrates and smaller values in insects or inferior eukaryotes. Northern blot analysis during oogenesis and early development revealed two transcripts with different expressions of pattern behavior. One of them is present in all stages analyzed, whereas the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 32 publications
3
45
0
Order By: Relevance
“…In Xenopus leavis, CNBP mRNA could be detected in the unfertilized eggs and in the embryonic cells derived from early ectoderm, endoderm, and mesoderm (Flink et al, 1998). In Bufo arenarum, Northern blot analysis revealed two transcripts with different expressions of pattern behaviour, and subcellular localization of CNBP was reported during oogenesis and early embryogenesis (Armas et al, 2001). During mouse embryogenesis, CNBP plays important roles in cell proliferation and tissue patterning during anterior -posterior axis, craniofacial and limb development by targeting c-Myc (Shimizua et al, 2003), and it is essential for the forebrain induction and specification .…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In Xenopus leavis, CNBP mRNA could be detected in the unfertilized eggs and in the embryonic cells derived from early ectoderm, endoderm, and mesoderm (Flink et al, 1998). In Bufo arenarum, Northern blot analysis revealed two transcripts with different expressions of pattern behaviour, and subcellular localization of CNBP was reported during oogenesis and early embryogenesis (Armas et al, 2001). During mouse embryogenesis, CNBP plays important roles in cell proliferation and tissue patterning during anterior -posterior axis, craniofacial and limb development by targeting c-Myc (Shimizua et al, 2003), and it is essential for the forebrain induction and specification .…”
Section: Introductionmentioning
confidence: 95%
“…It contains seven tandem zinc finger repeats that are composed of 14 same amino acid arrangement of Cys-X2 -Cys -X4 -His-X4 -Cys (Armas et al, 2001). So far, CNBP cDNAs have been cloned from human (Rajavashisth et al, 1989), mouse (Warden et al, 1994), rat (Yasuda et al, 1995), chicken (Van Heumen et al, 1997), Xenopus (Flink et al, 1998), Bufo arenarum (Armas et al, 2001), and Danio rerio (Armas et al, 2004), and all of them have been demonstrated to be highly conserved at the amino acid and nucleotide levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains seven tandem zinc finger repeats that are composed of 14 same amino acids of Cys-X2-Cys-X4-His-X4-Cys [2,3]. So far, CNBP cDNAs have been cloned from human [4], mouse [5], rat [6], chicken [7], Xenopus [8], Bufo arenarum [3], Danio rerio [9] and gibel carp [10], and all of them have been demonstrated to be highly conserved at the amino acid and nucleotide levels.…”
Section: Introductionmentioning
confidence: 99%
“…During embryogenesis, the CNBP expression patterns have been analyzed in Bufo arenarum, Xenopus leavis, Danio rerio, mouse and chick [3,8,9,[11][12][13]. During early embryogenesis, CNBP mRNA could be detected in the The nucleotide sequence data reported in this paper have been submitted to the GenBank under accession number: CagCNBP (AY773183).…”
Section: Introductionmentioning
confidence: 99%